Rehabilitasi Lahan di Tefa Pembibitan (Nursery) Polije Melalui Aplikasi Pupuk Blotong Untuk Meningkatkan Karbon Organik dan Total Bakteri Tanah - Anni Nuraisyah; Triono Bambang Irawan; Satria Indra Kusuma; Titien Fatimah (Journal of Community Development, 2025)
The TEFA Nursery under the Department of Agricultural Production at Polije was initiated in 2020. From 1990 to 2024, the practice land at the TEFA Nursery has been intensively used for the cultivation of food and plantation crops, leading to a decline in soil fertility and reduced crop yields. This community service activity aims to improve soil fertility by increasing organic carbon levels and total soil bacteria. The activities were carried out from July to August 2024, with the following stages: (i) Coordination and preparation; (ii) Material socialization at the TEFA Nursery; (iii) Application of blotong fertilizer; (iv) Technical guidance on the use of dry soil testing devices; and (v) Monitoring and evaluation. These activities assisted TEFA Nursery managers in planning and maintaining cultivated plants with higher yields and better quality.